Does Multitasking Affect Students' Academic Performance? Evidence From a Longitudinal Study - Simon Amez; Stijn Baert; Emily Heydencamp; Joey Wuyts (Global Labor Organization (GLO), 2021)
Multitasking - alternating between two different tasks at the same time - has become a daily habit for many university students. However, this may come at a cost since the existing literature emphasises the negative association between multitasking and academic performance. Nonetheless, this literature is based on cross-sectional observational data so that that estimates cannot be given a causal interpretation. To complement these studies, we opted for a longitudinal design in this study. Specifically, for three consecutive years, students at two Belgian universities, in more than ten different study programmes, were surveyed on their multitasking preferences and academic performance. Then, these results were merged with the students' exam scores. We exploited the longitudinal character of the data by running random and fixed effect models. Our results indicate that the positive and negative aspects of multitasking with respect to academic performance cancel each other out.
Keywords: 330; multitasking; academic performance; longitudinal data